- #1
Joseph1739
- 33
- 0
Not sure if this is the correct place to post this.
dy/dt = 0, find y(t)
My professor told me that the chain rule is used to determine that (dy/dt)*dt = dy, but I just don't see it.
Multiply both sides by dt.
(dy/dt)*dt = 0dt
(dy/dt)*dt = 0
dy = 0, then integrating both sides:
y = C
dy/dt is the derivative of the function y in respect to t, and dt is just a small change in t. How is the chain rule used here? dz/dx = dz/dy * dy/dx makes a lot more sense to me, but I just don't see that here.
dy/dt = 0, find y(t)
My professor told me that the chain rule is used to determine that (dy/dt)*dt = dy, but I just don't see it.
Multiply both sides by dt.
(dy/dt)*dt = 0dt
(dy/dt)*dt = 0
dy = 0, then integrating both sides:
y = C
dy/dt is the derivative of the function y in respect to t, and dt is just a small change in t. How is the chain rule used here? dz/dx = dz/dy * dy/dx makes a lot more sense to me, but I just don't see that here.